PENGEMBANGAN AGROWISATA, POTENSI INOVASI PRODUK DAN KONSUMSI PANGAN FUNGSIONAL JERUK SIOMPU DI KABUPATEN BUTON SELATAN - Helviani, Helviani; Basrin, Basrin; Juliatmaja, Aan Wilhan; Purbaningsih, Yul; Hasbiadi, Hasbiadi; Amin, Muhtar (AGRIBIOS, 2024)
Agrotourism development emphasises local culture in land use to increase farmers' income and preserve existing land resources. Agrotourism is an integrated system of activities designed to develop tourism and agriculture. This research aims to analyse the internal and external factors that influence the Siompu Orange Garden agrotourism development strategy and the Siompu Orange Garden agrotourism development strategy in South Buton Regency. The data analysis used is SWOT analysis. The results of this research state that the development of Siompu orange garden agrotourism in South Buton Regency has resulted in 5 core strategies, including; Strategy I is synergy between the community and agrotourism managers. Strategy II is improving facilities and infrastructure. Strategy III is increasing promotional activities. Strategy IV is increasing the size of the tourist area. Strategy V is partnership and collaboration.